PENGARUH FLUKTUASI HARGA EMAS DAN PROMOSI TERHADAP MINAT NASABAH PADA PRODUK TABUNGAN EMAS DI PEGADAIAN SYARIAH JELUTUNG - M.Nazori Madjid; Refky Fielnanda; Bela Sesarwati (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of gold price fluctuations and promotions on customer interest in gold savings products at the Jelutung Sharia Pawnshop. This study uses descriptive quantitative research methods. The research was conducted at the Office of PT. Pegadaian (Persero) Syariah which is located at Jl. DI Panjaitan No.30,Kebun Handil, Kec. Jelutung, Jambi City, Jambi. This study uses multiple regression analysis tools. This study uses a population of 2,151 customers of the gold tube of Pegadaian Syariah Jelutung Branch with sampling using the slovin formula which produces a sample of 100 customers. The results of this study are partially positive and significant effect of Price Fluctuations on Customer Interest in gold savings products at Pegadaian Syariah Jelutung. Promotion has an effect on customer interest in gold savings products at the Jelutung Sharia Pawnshop. Simultaneously, price fluctuations and promotions have an effect on customer interest in gold savings products at the Jelutung Sharia Pawnshop